2D Organic Nanosheets: Free‐Standing Buckle‐Delaminated 2D Organic Nanosheets with Enhanced Mechanical Properties and Multifunctionality (Adv. Mater. Interfaces 17/2019). Issue 17 (6th September 2019) - Zhang, Qiuting; Zhang, Zhuolei; Yin, Jie
Abstract : Highly stretchable organic conjugated polymeric nanosheet is realized through spontaneous periodic buckle‐delamination of transfer‐printed free‐stranding nanosheets on pre‐strained elastomers. The free‐standing nanosheet exhibits superior electronic, mechanical, and wetting properties to its counterpart spin‐coated wrinkled nanosheet, which are attributed to its distinct ordered chemical structures from spin coatings and buckle‐delamination. More details can be found in article number 1900561 by Qiuting Zhang, Zhuolei Zhang, and Jie Yin.